Penerapan Model Cooperative Integrated Reading and Composition dalam Pembelajaran Bahasa Indonesia di MI Al Ma’arif Gunung Pasir - Marida, Nurlaili; Fajri, Nurul; Nurma, Nurma (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Indonesian language learning at the Madrasah Ibtidaiyah (MI) level has an important role in improving students’ language skills, especially in reading and writing. However, many students still experience difficulties in understanding reading texts and writing effectively due to uninteresting learning methods and lack of active student involvement. One strategy that can be used to overcome this problem is the Cooperative Integrated Reading and Composition (CIRC) model, which integrates reading and writing skills in a series of learning activities based on group cooperation. This study aims to analyze the effectiveness of the CIRC model in improving reading comprehension and writing skills of grade V students of MI Al Ma’arif Gunung Pasir. The method used was Classroom Action Research (PTK) with two cycles, which involved planning, implementation, observation, and reflection. Data were collected through observation, interviews, and reading comprehension and writing tests before and after the application of the CIRC model. The results showed that the implementation of the CIRC model significantly improved students’ reading comprehension and writing skills. Students are easier to understand the content of reading through group discussions, as well as more skillful in composing systematic and communicative writing. In addition, this model also increases learning motivation, social skills, and cooperation among students. Thus, the CIRC model is recommended